Maintaining the Originality of Ancestral Belief; Ethnographic Study of the Lom Belief System of the Mapur Bangka Tribe - Janawi; Nikmarijal (International Journal of Psychosocial Rehabilitation, 2020)
The Lom people of the Mapur Bangka tribe are unique and hold on to ancestral beliefs. The originality of their customs is based on the principles and foundations of ancestral views, holding on to the taboo rituals, including the sacred and profane matters. However, they settled and interacted with religious communities, including Islam (the majority), Christians, and Confucians. This is an ethnographic study of the Lom customs with a religious anthropology approach. Data retrieval involved observation and in-depth interviews with key informants, including the Customary Chairperson, leaders, and Lom communities. Data collection was carried out in the Lom Mapur residential area, such as Air Abik, Mapur, and Pejem in Bangka regency. The finding of the study indicated that Orang Lom maintains the ancestral belief system, which is primarily animism and identical to fetishism. They used an ambiguous strategy between ownership of formal citizenship and trust identities. The ambiguity of identity was formulated for the adherents of local religions in Indonesia. Although there was a change in way of life, they still maintained their traditional customs. In general, ancestral trust was a rule, norm, and guideline in understanding cosmology, including legends and hereditary myths. According to the people, it is not necessary to adopt a formal religion. The happiness of life is not determined by the religion but rather by a clean heart.